Preparation method of spirogyra-based carbon electrode material

By using water sponge to prepare carbon electrode materials, combined with hydrothermal technology and catalyst treatment, a multi-stage pore structure is formed and N and S atoms doped, the balance problem of the energy density and power density of the electrode material in the prior art is solved, and a carbon electrode material with high specific capacitance and excellent electrical properties is achieved.

CN119774606APending Publication Date: 2025-04-08NANJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510083606.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

While the existing supercapacitor electrode materials increase the energy density, it is difficult to maintain high power density and cycle life, and there are still problems in improving the performance of carbon electrode materials.

Method used

Water sponge is used as the precursor of carbon material. Through the use of hydrothermal technology and catalysts, the surface structure of carbon material is adjusted and modified, combined with pyrolysis activation technology, a carbon electrode material with a multi-stage pore structure is formed, and N and S atoms are doped to improve the specific capacitance.

Benefits of technology

The prepared water-sponge-based carbon electrode material has a multi-stage pore structure, excellent electrical properties and high specific capacitance, and can achieve high-performance energy storage under low cost and industrial production conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a spirogyra-based carbon electrode material. The method comprises the following steps: taking waste spirogyra, carrying out ultrasonic cleaning with deionized water, and carrying out vacuum drying; mixing the dried spirogyra with NH4HSO4, adding deionized water, uniformly stirring, and putting into a reaction kettle for hydrothermal reaction; after the reaction is finished, centrifugally filtering to obtain a solid product, soaking with pure ethanol, cleaning with deionized water, drying, then putting into an activating agent, continuously stirring for 18 hours, filtering, drying, putting into a tubular furnace, and introducing CO2 gas for heating; and after reacting for a certain time, cooling a product to room temperature, soaking with an acid solution, continuously stirring for 4 hours, repeatedly washing with ethanol and deionized water to be neutral, and drying to obtain the spirogyra-based carbon electrode material. The method is simple in preparation process, low in cost, easy to repeat and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new energy material preparation, and specifically relates to a method for preparing a sponge-based carbon electrode material. Background Art

[0002] Spirogyra is a kind of aquatic algae plant that likes to grow in static water bodies rich in organic matter, such as ponds, ditches, rivers, etc. Its eutrophication will cause flooding, seriously endangering the growth of rice and the photosynthesis of lotus roots, and may also produce unpleasant odors and reduce water quality. Its effective treatment and utilization is not only of great significance to the ecological environment, but also has reference value for the rational utilization of renewable biomass resources.

[0003] At present, supercapacitors are considered to be one of the potential energy storage systems because of their advantages of high power density, fast charge and discharge process, environmental friendliness, good safety and stability, etc. They can be used in portable electronic devices, backup energy systems and military fields. At the same time, supercapacitors can also be mixed with lithium-ion batteries or fuel cells for hybrid vehicles, as well as some large-scale power and energy systems.

[0004] In order to meet the demand for supercapacitor energy density of high-performance energy storage devices, an effective method is to increase the energy density of capacitors by increasing the specific capacity of carbon materials used as electrode materials, because this will not lose the power density and cycle life of capacitors. The specific capacity of carbon materials can be improved by designing and regulating the pore structure of carbon materials to provide low resistance channels for electron transmission and ion diffusion, and by reducing internal resistance and increasing the contact area between electrodes and electrolytes. It is worth noting that increasing the degree of graphitization of materials can greatly improve the conductivity of carbon materials, thereby reducing the internal resistance of materials, but significantly reducing the specific surface area of ​​materials, and loading heteroatoms (N, F, B, S or P) on the carbon framework can significantly improve the specific capacity of carbon-based materials. Selecting suitable carbon-based precursors to improve the performance of carbon electrode materials using reasonable technologies is still a difficult problem to be overcome in this field.

[0005] Spirogyra is cheap and easy to obtain. It is rich in heteroatoms such as N and P. By using hydrothermal technology and selecting suitable catalysts, the surface structure of Spirogyra-based carbon materials can be effectively adjusted and modified. Combined with pyrolysis activation, it promotes the formation and development of the void structure of carbon materials, thereby improving the performance of carbon electrode materials. The process is simple and the early application period is broad. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a water sponge-based carbon electrode material, which has a simple preparation process, low cost, easy repetition, and is suitable for industrial production. The prepared water sponge-based carbon material has a multi-level pore structure and retains the biomass carbon skeleton. The doped N atoms provide a high pseudocapacitive specific capacity, improve the ion permeability and conductivity of the material, and make it have a large specific surface area and excellent electrical properties.

[0007] Specifically, the technical solution of the present invention relates to a method for preparing a supercapacitor electrode material, comprising the following steps: Step A: Take the discarded Spirogyra, add deionized water, and perform ultrasonic cleaning for 5 to 6 times, each time for 20 to 40 minutes, until the solution is clear, filter and dry under vacuum at 60°C for 12 hours to obtain dry Spirogyra; Step B: Mix the dried Spirogyra in step A with NH4HSO4, add deionized water and stir evenly, place the mixed solution in a reactor with a polytetrafluoroethylene liner and a filling ratio of 50% to 70%, heat to 170-220°C at a rate of 10°C / min and react for 16-24 hours, naturally cool to room temperature after the reaction, centrifuge at a speed of 2000-3000 rpm for 30-60 minutes, separate the precipitate from the supernatant, and then filter to obtain a solid product, immerse in pure ethanol for 24 hours, rinse with deionized water until the filtrate is clear, and vacuum dry at 60°C for 12 hours to obtain a carbon-based solid product; Step C: The carbon-based solid product obtained in step B is immersed in an activator at room temperature and stirred continuously for 18 hours, filtered, dried at 60°C in vacuum for 12 hours, placed in a tube furnace, the tube furnace is sealed and CO2 gas is introduced, heated to a certain temperature at a constant heating rate, and kept warm for 2 hours to obtain a preliminary water-sponge-based porous carbon material; Step D: After the preliminary sponge-based porous carbon material obtained in step C is naturally cooled to room temperature, it is soaked in an acidic solution and stirred continuously for 4 hours, then repeatedly washed with ethanol and deionized water in turn until neutral, and vacuum dried at 60°C for 12 hours to obtain the final sponge-based carbon electrode material.

[0008] Furthermore, the waste Spirogyra in step A is Spirogyra growing in fresh water at any growth stage; the ultrasonic cleaning frequency is 29-35 kHz, and the power is 22-26 W / L.

[0009] Furthermore, in step B, the mixture of dried Spirogyra, NH4HSO4 and deionized water is stirred for 60-180 min, and the stirring speed is 500-1000 r / min.

[0010] Furthermore, in step B, the mass ratio of dried Spirogyra, NH4HSO4 and deionized water is 2:1:20 to 2:2:40.

[0011] Furthermore, the vacuum degree of vacuum drying in step B, step C and step D is 19000Pa.

[0012] Furthermore, in step C, the activator is a ZnCl2 solution, and the mass ratio of the carbon-based solid product to ZnCl2 is 1:1 to 2:1.

[0013] Furthermore, in step C, the stirring speed is 2000-4000 r / min.

[0014] Furthermore, in step C, the CO2 gas flow rate is 1 L / min, the heating rate is 4-10°C / min, the temperature is raised to 600-700°C and kept warm for 2 hours.

[0015] Furthermore, in step D, the acidic solution is a 0.1 mol / L boric acid solution, the immersion temperature is 60-80° C., and the stirrer speed is 1000-1500 r / min. Beneficial Effects

[0016] 1. The present invention uses Spirogyra waste as a carbon material precursor. The raw material is easily available, low in cost, has a unique nano-micro dual structure, and is rich in nitrogen and phosphorus impurities. When using it to prepare carbon electrode materials, it is conducive to the doping of nitrogen and sulfur impurities. 2. The ammonium bisulfate used in the present invention is acidic, which is convenient for catalyzing the organic reaction of Spirogyra, promoting the embedding of nitrogen and sulfur into porous carbon, improving the stability of Spirogyra-based carbon, and increasing its specific capacitance; 3. In the process of preparing carbon electrode materials using Spirogyra, the present invention adopts a vacuum drying process, which can protect the surface structure and original chemical properties of the heteroatom-doped carbon material to the maximum extent; 4. In the process of heteroatom doping of the sponge-based carbon material, the present invention adopts a boric acid soaking method, which is beneficial to the separation of the mixture and the recycling of boric acid, while realizing the loading of the boron element at low temperature, and the prepared electrode material has excellent electrochemical properties.

[0017] 5. The water sponge-based carbon electrode material prepared by the present invention has a multi-level pore structure and retains the biomass carbon skeleton. The doped N and S atoms provide a high pseudocapacitive specific capacity, improve the ion permeability and conductivity of the material, and make it have a large specific surface area and excellent electrical properties. DETAILED DESCRIPTION

[0018] The preparation method of a sponge-based carbon electrode material of the present invention is further described and explained below in conjunction with various embodiments.

[0019] A method for preparing a sponge-based carbon electrode material of the present invention comprises the following steps: Step A: Take waste Spirogyra, add deionized water, and perform ultrasonic cleaning for 5 to 6 times, each time for 20 to 40 minutes, the ultrasonic cleaning frequency range is 29 to 35 kHz, and the power range is 22 to 26 W / L; until the solution is clear, filter it, and then vacuum dry it at 60° C. for 12 hours to obtain dried Spirogyra; the waste Spirogyra in the present invention is Spirogyra growing in any growth period in freshwater bodies.

[0020] Step B: Mix the dried Spirogyra in step A with NH4HSO4, add deionized water and stir evenly, stir for 60 min ~180 min, and the speed range of the stirrer is 500~1000r / min; place the mixed solution in a reactor with a polytetrafluoroethylene liner and a filling ratio of 50%~70%, heat it to 170~220℃ at a rate of 10℃ / min and react for 16~24 hours, naturally cool to room temperature after the reaction, centrifuge at a speed of 2000~3000 rpm for 30 min ~60 min, separate the precipitate from the supernatant, and then filter to obtain a solid product, immerse it in pure ethanol for 24 hours, rinse with deionized water until the filtrate is clear, and vacuum dry it at 60℃ for 12 hours with a vacuum degree of 19000Pa; obtain a carbon-based solid product; wherein the mass ratio of dried Spirogyra, NH4HSO4 and deionized water is 2:1:20~2:2:40.

[0021] Step C: soak the carbon-based solid product obtained in step B in an activator at room temperature and stir continuously for 18 hours at a stirring speed of 2000-4000 r / min; the activator is a ZnCl2 solution, and the mass ratio of the carbon-based solid product to ZnCl2 is 1:1-2:1; filter, dry at 60°C in vacuum for 12 hours, and the vacuum degree is 19000Pa; put it in a tubular furnace, close the tubular furnace and introduce CO2 gas, heat it to a certain temperature at a constant heating rate, the CO2 gas flow rate is 1L / min, the heating rate is 4-10°C / min, heat it to 600-700°C and keep it warm for 2 hours, and obtain a preliminary sponge-based porous carbon material; Step D: After the preliminary sponge-based porous carbon material obtained in step C is naturally cooled to room temperature, it is soaked in an acidic solution and stirred continuously for 4 hours, the acidic solution is a 0.1 mol / L boric acid solution, the soaking temperature is 60-80°C, and the stirrer speed is 1000-1500 r / min; then it is repeatedly washed with ethanol and deionized water in turn until neutral, and vacuum dried at 60°C for 12 hours, and the vacuum degree is 19000 Pa; the final sponge-based carbon electrode material is obtained.

[0022] In order to better understand the present invention, the present invention is further described in detail below through examples. Embodiment 1

[0023] Take the discarded Spirogyra, add deionized water, and ultrasonically clean it 6 times, each time for 40 minutes. The ultrasonic cleaning frequency is 29kHz and the power is 22W / L. When the solution is clear, filter to obtain clean Spirogyra, and vacuum dry it for 12 hours. Mix 20 grams of dried Spirogyra with 20 grams of NH4HSO4, add 400 grams of deionized water, stir for 60 minutes, and the stirrer speed is 500r / min. Place the mixed solution in a reactor with a polytetrafluoroethylene liner and a filling ratio of 50% to 70%, heat it to 170℃ at a rate of 10℃ / min and react for 24 hours. After the reaction is completed, naturally cool it to room temperature, centrifuge it at a speed of 3000r / min for 60 minutes, separate the precipitate from the supernatant, filter to obtain a solid product, immerse it in pure ethanol for 24 hours, rinse it with deionized water until the filtrate is clear, and vacuum dry it at 60℃ for 12 hours to obtain a carbon-based solid product. Take 5 grams of the obtained carbon-based solid product, soak it in a solution containing 5 grams of ZnCl2 at room temperature, stir it continuously for 18 hours, the stirrer speed is 2000r / min, filter it, vacuum dry it at 60℃ for 12 hours, put it into a tube furnace, close the tube furnace and pass CO2 gas, the gas flow rate is 1L / min, the heating rate is 4℃ / min, heat it to 600℃ and keep it warm for 2 hours, and obtain a preliminary sponge-based porous carbon material. After cooling naturally to room temperature, soak it in 0.1mol / L boric acid solution at 60℃, the stirrer speed is 1000r / min, soak it for 4 hours, then wash it repeatedly with ethanol and deionized water to neutrality, vacuum dry it at 60℃ for 12 hours, and obtain the final sponge-based carbon electrode material.

[0024] Cyclic voltammetry tests show that at a current density of 1A / g, the specific capacitance is 320.1F / g, and it can still maintain 307.2F / g after 1000 cycles of charge and discharge. Embodiment 2

[0025] Take the discarded Spirogyra, add deionized water, and ultrasonically clean it 5 times, each time for 20 minutes. The ultrasonic cleaning frequency is 35kHz and the power is 26W / L. When the solution is clear, filter to obtain clean Spirogyra, and vacuum dry it for 12 hours. Mix 20 grams of dried Spirogyra with 10 grams of NH4HSO4, add 200 grams of deionized water, stir for 180 minutes, and the stirrer speed is 1000r / min. Place the mixed solution in a reactor with a polytetrafluoroethylene liner and a filling ratio of 50% to 70%, heat it to 220℃ at a rate of 10℃ / min and react for 16 hours. After the reaction is completed, naturally cool it to room temperature, centrifuge it at a speed of 2000r / min for 30 minutes, separate the precipitate from the supernatant, filter it to obtain a solid product, immerse it in pure ethanol for 24 hours, rinse it with deionized water until the filtrate is clear, and vacuum dry it at 60℃ for 12 hours to obtain a carbon-based solid product. Take 5 grams of the obtained carbon-based solid product, soak it in a solution containing 5 grams of ZnCl2 at room temperature, stir it continuously for 18 hours, the stirrer speed is 2000r / min, filter it, vacuum dry it at 60℃ for 12 hours, put it into a tube furnace, close the tube furnace and pass CO2 gas, the gas flow rate is 1L / min, the heating rate is 4℃ / min, heat it to 600℃ and keep it warm for 2 hours, and obtain a preliminary sponge-based porous carbon material. After cooling naturally to room temperature, soak it in 0.1mol / L boric acid solution at 60℃, the stirrer speed is 1000r / min, soak it for 4 hours, then wash it repeatedly with ethanol and deionized water to neutrality, vacuum dry it at 60℃ for 12 hours, and obtain the final sponge-based carbon electrode material.

[0026] Cyclic voltammetry tests show that at a current density of 1A / g, the specific capacitance is 335.5F / g, and it can still maintain 322.2F / g after 1000 cycles of charge and discharge. Embodiment 3

[0027] Take the discarded Spirogyra, add deionized water, and ultrasonically clean it 5 times, each time for 20 minutes. The ultrasonic cleaning frequency is 29kHz and the power is 26W / L. When the solution is clear, filter to obtain clean Spirogyra, and vacuum dry it for 12 hours. Mix 20 grams of dried Spirogyra with 10 grams of NH4HSO4, add 200 grams of deionized water, stir for 180 minutes, and the stirrer speed is 1000r / min. Place the mixed solution in a reactor with a polytetrafluoroethylene liner and a filling ratio of 50% to 70%, heat it to 220℃ at a rate of 10℃ / min and react for 16 hours. After the reaction is completed, naturally cool it to room temperature, centrifuge it at a speed of 2000r / min for 30 minutes, separate the precipitate from the supernatant, filter it to obtain a solid product, immerse it in pure ethanol for 24 hours, rinse it with deionized water until the filtrate is clear, and vacuum dry it at 60℃ for 12 hours to obtain a carbon-based solid product. Take 5 grams of the obtained carbon-based solid product, soak it in a solution containing 2.5 grams of ZnCl2 at room temperature, stir it continuously for 18 hours, the stirrer speed is 4000r / min, filter it, vacuum dry it at 60℃ for 12 hours, put it into a tube furnace, close the tube furnace and pass CO2 gas, the gas flow rate is 1L / min, the heating rate is 4℃ / min, heat it to 700℃ and keep it for 2 hours to obtain a preliminary sponge-based porous carbon material. After cooling naturally to room temperature, soak it in 0.1mol / L boric acid solution at 60℃, the stirrer speed is 1000r / min, soak it for 4 hours, then wash it repeatedly with ethanol and deionized water to neutrality, vacuum dry it at 60℃ for 12 hours to obtain the final sponge-based carbon electrode material.

[0028] Cyclic voltammetry tests show that at a current density of 1A / g, the specific capacitance is 327.6F / g, and it can still maintain 314.5F / g after 1000 cycles of charge and discharge. Embodiment 4

[0029] Take the discarded Spirogyra, add deionized water, and ultrasonically clean it 6 times, each time for 20 minutes. The ultrasonic cleaning frequency is 35kHz and the power is 22W / L. When the solution is clear, filter to obtain clean Spirogyra, and vacuum dry it for 12 hours. Mix 20 grams of dried Spirogyra with 10 grams of NH4HSO4, add 200 grams of deionized water, stir for 180 minutes, and the stirrer speed is 1000r / min. Place the mixed solution in a reactor with a polytetrafluoroethylene liner and a filling ratio of 50% to 70%, heat it to 170℃ at a rate of 10℃ / min and react for 16 hours. After the reaction is completed, naturally cool it to room temperature, centrifuge it at a speed of 1000r / min for 30 minutes, separate the precipitate from the supernatant, filter it to obtain a solid product, immerse it in pure ethanol for 24 hours, rinse it with deionized water until the filtrate is clear, and vacuum dry it at 60℃ for 12 hours to obtain a carbon-based solid product. Take 5 grams of the obtained carbon-based solid product, soak it in a solution containing 2.5 grams of ZnCl2 at room temperature, stir it continuously for 18 hours, the stirrer speed is 4000r / min, filter it, vacuum dry it at 60℃ for 12 hours, put it into a tube furnace, close the tube furnace and pass CO2 gas, the gas flow rate is 1L / min, the heating rate is 4℃ / min, heat it to 600℃ and keep it warm for 2 hours, and obtain a preliminary sponge-based porous carbon material. After cooling naturally to room temperature, soak it in 0.1mol / L boric acid solution at 60℃, the stirrer speed is 1000r / min, soak it for 4 hours, then wash it repeatedly with ethanol and deionized water to neutrality, vacuum dry it at 60℃ for 12 hours, and obtain the final sponge-based carbon electrode material.

[0030] Cyclic voltammetry tests show that at a current density of 1A / g, the specific capacitance is 308.9F / g, and it can still maintain 295.5F / g after 1000 cycles of charge and discharge. Embodiment 5

[0031] Take the discarded Spirogyra, add deionized water, and ultrasonically clean it 6 times, each time for 20 minutes. The ultrasonic cleaning frequency is 35kHz and the power is 22W / L. When the solution is clear, filter to obtain clean Spirogyra, and vacuum dry it for 12 hours. Mix 20 grams of dried Spirogyra with 20 grams of NH4HSO4, add 400 grams of deionized water, stir for 180 minutes, and the stirrer speed is 1000r / min. Place the mixed solution in a reactor with a polytetrafluoroethylene liner and a filling ratio of 50% to 70%, heat it to 220℃ at a rate of 10℃ / min and react for 24 hours. After the reaction is completed, naturally cool it to room temperature, centrifuge it at a speed of 2000r / min for 30 minutes, separate the precipitate from the supernatant, filter it to obtain a solid product, immerse it in pure ethanol for 24 hours, rinse it with deionized water until the filtrate is clear, and vacuum dry it at 60℃ for 12 hours to obtain a carbon-based solid product. Take 5 grams of the obtained carbon-based solid product, soak it in a solution containing 2.5 grams of ZnCl2 at room temperature, stir it continuously for 18 hours, the stirrer speed is 4000r / min, filter it, vacuum dry it at 60℃ for 12 hours, put it into a tube furnace, close the tube furnace and pass CO2 gas, the gas flow rate is 1L / min, the heating rate is 4℃ / min, heat it to 700℃ and keep it for 2 hours to obtain a preliminary sponge-based porous carbon material. After cooling naturally to room temperature, soak it in 0.1mol / L boric acid solution at 60℃, the stirrer speed is 1000r / min, soak it for 4 hours, then wash it repeatedly with ethanol and deionized water to neutrality, vacuum dry it at 60℃ for 12 hours to obtain the final sponge-based carbon electrode material.

[0032] Cyclic voltammetry tests show that at a current density of 1A / g, the specific capacitance is 337.9F / g, and it can still maintain 325.1F / g after 1000 cycles of charge and discharge. Embodiment 6

[0033] Take the discarded Spirogyra, add deionized water, and ultrasonically clean it 5 times, each time for 20 minutes. The ultrasonic cleaning frequency is 35kHz and the power is 22W / L. When the solution is clear, filter to obtain clean Spirogyra, and vacuum dry it for 12 hours. Mix 20 grams of dried Spirogyra with 20 grams of NH4HSO4, add 300 grams of deionized water, stir for 180 minutes, and the stirrer speed is 1000r / min. Place the mixed solution in a reactor with a polytetrafluoroethylene liner and a filling ratio of 50% to 70%, heat it to 170℃ at a rate of 10℃ / min and react for 24 hours. After the reaction is completed, cool it naturally to room temperature, centrifuge it at a speed of 3000r / min for 60 minutes, separate the precipitate from the supernatant, filter to obtain a solid product, immerse it in pure ethanol for 24 hours, rinse it with deionized water until the filtrate is clear, and vacuum dry it at 60℃ for 12 hours to obtain a carbon-based solid product. Take 5 grams of the obtained carbon-based solid product, soak it in a solution containing 2.5 grams of ZnCl2 at room temperature, stir it continuously for 18 hours, the stirrer speed is 2000r / min, filter it, vacuum dry it at 60℃ for 12 hours, put it into a tube furnace, close the tube furnace and pass CO2 gas, the gas flow rate is 1L / min, the heating rate is 4℃ / min, heat it to 700℃ and keep it for 2 hours to obtain a preliminary water-sponge-based porous carbon material. After cooling naturally to room temperature, soak it in 0.1mol / L boric acid solution at 80℃ and 1500r / min, soak it for 4 hours, then wash it repeatedly with ethanol and deionized water to neutrality, vacuum dry it at 60℃ for 12 hours to obtain the final water-sponge-based carbon electrode material.

[0034] Cyclic voltammetry tests show that at a current density of 1A / g, the specific capacitance is 328.6F / g, and it can still maintain 314.2F / g after 1000 cycles of charge and discharge. Embodiment 7

[0035] Take the discarded Spirogyra, add deionized water, and ultrasonically clean it 5 times, each time for 30 minutes. The ultrasonic cleaning frequency is 32kHz and the power is 24W / L. When the solution is clear, filter to obtain clean Spirogyra, and vacuum dry it for 12 hours. Mix 20 grams of dried Spirogyra with 15 grams of NH4HSO4, add 250 grams of deionized water, stir for 180 minutes, and the stirrer speed is 1000r / min. Place the mixed solution in a reactor with a polytetrafluoroethylene liner and a filling ratio of 50% to 70%, heat it to 220℃ at a rate of 10℃ / min and react for 20 hours. After the reaction is completed, cool it naturally to room temperature, centrifuge it at a speed of 2000r / min for 30 minutes, separate the precipitate from the supernatant, filter to obtain a solid product, immerse it in pure ethanol for 24 hours, rinse it with deionized water until the filtrate is clear, and vacuum dry it at 60℃ for 12 hours to obtain a carbon-based solid product. Take 5 grams of the obtained carbon-based solid product, soak it in a solution containing 4 grams of ZnCl2 at room temperature, stir it continuously for 18 hours, the stirrer speed is 3000r / min, filter it, vacuum dry it at 60℃ for 12 hours, put it into a tube furnace, close the tube furnace and pass CO2 gas, the gas flow rate is 1L / min, the heating rate is 4℃ / min, heat it to 650℃ and keep it for 2 hours to obtain a preliminary water-sponge-based porous carbon material. After cooling naturally to room temperature, soak it in 0.1mol / L boric acid solution at 70℃ and 1200r / min, soak it for 4 hours, then wash it repeatedly with ethanol and deionized water to neutrality, vacuum dry it at 60℃ for 12 hours to obtain the final water-sponge-based carbon electrode material.

[0036] Cyclic voltammetry tests show that at a current density of 1A / g, the specific capacitance is 338.2F / g, and it can still maintain 323.8F / g after 1000 cycles of charge and discharge.

[0037] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a sponge-based carbon electrode material, characterized in that: The following steps are involved: Step A: Take the discarded Spirogyra, add deionized water, and perform ultrasonic cleaning for 5 to 6 times, each time for 20 to 40 minutes, until the solution is clear, filter and dry under vacuum at 60°C for 12 hours to obtain dry Spirogyra; Step B: Mix the dried Spirogyra in step A with NH4HSO4, add deionized water and stir evenly, place the mixed solution in a reactor with a polytetrafluoroethylene liner and a filling ratio of 50% to 70%, heat to 170-220°C at a rate of 10°C / min and react for 16-24 hours, naturally cool to room temperature after the reaction, centrifuge at a speed of 2000-3000 rpm for 30-60 minutes, separate the precipitate from the supernatant, and then filter to obtain a solid product, immerse in pure ethanol for 24 hours, rinse with deionized water until the filtrate is clear, and vacuum dry at 60°C for 12 hours to obtain a carbon-based solid product; Step C: The carbon-based solid product obtained in step B is immersed in an activator at room temperature and continuously stirred for 18 hours, filtered, dried at 60°C in vacuum for 12 hours, placed in a tube furnace, the tube furnace is sealed and CO2 gas is introduced, heated to a preset temperature at a constant heating rate, and kept warm for 2 hours to obtain a preliminary water-sponge-based porous carbon material; Step D: After the preliminary sponge-based porous carbon material obtained in step C is naturally cooled to room temperature, it is soaked in an acidic solution and stirred continuously for 4 hours, then repeatedly washed with ethanol and deionized water in turn until neutral, and vacuum dried at 60°C for 12 hours to obtain the final sponge-based carbon electrode material.

2. The method for preparing a sponge-based carbon electrode material according to claim 1, characterized in that The waste Spirogyra in step A is Spirogyra growing in fresh water at any growth stage; the ultrasonic cleaning frequency range is 29-35 kHz, and the power range is 22-26 W / L.

3. The method for preparing a sponge-based carbon electrode material according to claim 1, characterized in that The mixture of dried Spirogyra, NH4HSO4 and deionized water in step B is stirred for 60-180 min, and the stirring speed range of the stirrer is 500-1000 r / min.

4. The method for preparing a sponge-based carbon electrode material according to claim 1, characterized in that In the step B, the mass ratio of dried Spirogyra, NH4HSO4 and deionized water is 2:1:20 to 2:2:

40.

5. The method for preparing a sponge-based carbon electrode material according to claim 1, characterized in that The vacuum degree of vacuum drying in step B, step C and step D is 19000Pa.

6. The method for preparing a sponge-based carbon electrode material according to claim 1, characterized in that In the step C, the activator is a ZnCl2 solution, and the mass ratio of the carbon-based solid product to ZnCl2 is 1:1 to 2:

1.

7. The method for preparing a sponge-based carbon electrode material according to claim 1, characterized in that The stirring speed in step C is 2000-4000 r / min.

8. The method for preparing a sponge-based carbon electrode material according to claim 1, characterized in that The CO2 gas flow rate introduced in step C is 1 L / min, the heating rate is 4-10°C / min, and the temperature is raised to 600-700°C.

9. The method for preparing a sponge-based carbon electrode material according to claim 1, characterized in that In the step D, the acidic solution is a 0.1 mol / L boric acid solution, the immersion temperature is 60-80° C., and the stirrer speed is 1000-1500 r / min.